2019
DOI: 10.3389/fendo.2019.00264
|View full text |Cite|
|
Sign up to set email alerts
|

Hypogonadism and Sexual Dysfunction in Testicular Tumor Survivors: A Systematic Review

Abstract: Testicular tumor is the most common malignancy in men of reproductive age. According to the tumor histology and staging, current treatment options include orchiectomy alone or associated with adjuvant chemo- and/or radiotherapy. Although these treatments have considerably raised the percentage of survivors compared to the past, they have been identified as risk factors for testosterone deficiency and sexual dysfunction in this subgroup of men. Male hypogonadism, in turn, predisposes to the development of metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 59 publications
1
27
0
2
Order By: Relevance
“…However, most of the previous studies were conducted without comparison of groups. In addition, multiple tools were used to assess erection function in different studies, which made comparison of the results a great chal- 2 Arch Med Sci lenge. Moreover, a systematic review including 36 studies demonstrated that male erectile disorder occurred in 11.5% of TC survivors [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies were conducted without comparison of groups. In addition, multiple tools were used to assess erection function in different studies, which made comparison of the results a great chal- 2 Arch Med Sci lenge. Moreover, a systematic review including 36 studies demonstrated that male erectile disorder occurred in 11.5% of TC survivors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hypogonadism also increases the risk of developing metabolic syndrome, including cardiovascular complications and diabetes, which appears to be greater after combination therapy (chemo-radiotherapy) ( 111 , 112 ). Research is currently underway to evaluate the impact of testosterone administration in long-term TC survivors, but results are still somewhat discordant ( 113 116 ).…”
Section: Stress-induced Immunosenescence In Testicular Cancer Survivomentioning
confidence: 99%
“…2 More than 95% of testicular tumors are diagnosed as testicular germ cell tumors (TGCTs). 3 Germ cell tumors (GCT) comprise of *98% of TCs. 4 Other GCTs include stromal tumors (2%), such as Leydig cell (*0.2%) and Sertoli cell tumors (*0.1).…”
mentioning
confidence: 99%
“…29 Kenney et al 29 reported that 20% of young adult male cancer patients experienced erectile dysfunction subsequent to treatment, and these findings were supported by several other studies revealing that more than half of all survivors presented with ejaculatory dysfunction following treatment. 3,30 These consequential reproductive outcomes, in relation to fatherhood, can have a detrimental effect on a patient's physical and psychological wellbeing, maintaining relationships, and quality of life. 31 Hence, discussion and counseling around sexuality, reproductive function, and fertility preservation are important before starting gonadotoxic treatment.…”
mentioning
confidence: 99%